HYPOXIC ISCHEMIC ENCEPHALOPATHY IN NEONATES - Qureshi, Azhar Munir; Rehman, Anees ur; Siddiqi, Tahir Saeed (Journal of Ayub Medical College Abbottabad, 2010)
Background: Birth anoxia remains an important cause of mortality and morbidity in neonates. Hypoxia/ischemia can lead to permanent brain damage and also affects other tissues of the body. It results from lack of oxygen before, during or after birth. The study was designed to assess the risk factors of birth asphyxia, common presentations and association of Apgar score with grades of hypoxic-ischemic encephalopathy. Methods: the study is descriptive, prospective and carried out in the Paediatric Department of Ayub Teaching Hospital, Abbottabad from September 2007 till September 2008. A total number of 181 neonates (144 males and 37 females) who showed the neurological signs of hypoxic-ischemic encephalopathy were included in the study. Maternal history was taken, Apgar scoring was done and neurological grading was done for the assessment of brain damage. Results: out of 181 neonates 77.9% were full term, 8.8% were premature, 5.2% were having intra uterine growth retardation and 6.1% were post mature. 38.7% were diagnosed as having grade-3, 38.7% as grade-2 and 22.6% as grade-1 encephalopathy. Mortality due to hypoxic ischemic encephalopathy in our unit was 16%. 52.5% of the mothers were primigravida, 50% of the multigravid mothers had history of perinatal deaths, and 6.1% had ante-natal examination. Antenatal factors like lack of antenatal examinations, toxaemia of pregnancy and prolonged labour were major contributors to the mortality of neonates. Conclusion: Primigravid mothers, maternal anaemia, lack of antenatal examination, toxaemia of pregnancy and prolonged labour were the major contributors to the hypoxic ischemic encephalopathy. Early recognition of the risk factors and public health awareness needs to be addressed. Improvements in maternal health and regular antenatal checkups should be emphasised. Key words: Hypoxic ischemic encephalopathy, risk factors, birth asphyxia.